Learning how to play in a band : Feminist intersectional action research of Srey’s School of Rock in Cambodia - Mäkinen, Paula (My University, 2023)
This study is an action research about the music workshop for women, Srey’s School of Rock, located in Cambodia. The focus in this study is to understand what can be learned for the benefit of the future of SSR from the observations that were conducted. To reach this understanding I ask these questions: Which ways did we found for teaching the instruments and band activities to participants, and what cultural aspects there were involved, as we were working in this certain location. The research material been collected in the workshop that was a pilot version of SSR in December 2016. The research material includes my fieldwork diary, pictures, videos, a short documentary and recording of the song done during the workshop. To make the study more broad, my supporting material includes some other types of research of Cambodian women. In the workshop I was reflecting the ways of learning through learning styles of popular musicians. We saw it important to think about the principles of safe space. A safer learning environment with room for trial and error is crucial and a practice band offered mostly this kind of environment for the participants of this workshop. Feminist activism in Cambodia seems to contain specific issues. Women seem to find it more difficult to engage in recreational activities, due to assumptions about them and stricter codes of conduct. In the Cambodian context, it would be important to earn an income from playing music. In Cambodia, the revival of music culture can have a special meaning, due to the recent history. As ways to develop the future SSR workshop, we could apply more of the life skills and peer directed learning, that already were present in the workshop. There would be benefits in cultivating this towards a more economically driven empowerment project, but to keep in mind the value of recreational activities as such. The tourism connected to this kind of workshop more strongly would bring mutual benefits for participants and for instructors, probably international. The interpreter would be needed, to make this even more empowering, and it should be also considered to make this partly or completely an online activity, to diminish the negative effects of flying. Also, it would be important to follow the results of empowerment and support participants as empowered agents. We should be more sensitive to different gender identities.
Keywords: women musicians, activism, DIY, Cambodia, empowerment, feminism